ANALYSIS OF HUMOR LANGUAGE IN “NGENEST THE MOVIE” COMEDY SCENE - Natanael, Christian; Annita, Annita (VCD: Journal of Visual Communication Design, 2022)
Humor language is verbal humor created through words, the meaning of words, and jargon. Directors use language humor to build comedy scenes, introduce the characters, or give the impression of a scene. However, sometimes, excessive techniques will be insufficient for the scene itself. Therefore, this study aims to find how language humor in comedy scenes in a film is overused and eventually dries the comedy. Research material was selected from a comedy movie entitled "Ngenest," produced in 2015, directed by Ernest Prakasa, who has a comical background and often uses comedic techniques in his films. The research method chosen is qualitative, with content analysis to identify the value of integrated humor and scenes in the movie "Ngenest.” Keywords: humor, humor language, scene, comedy